Rekonstruksi formula perhitungan kompensasi bagi usaha perikanan budidaya yang terdampak pencemaran laut - Ali Mashar mashar; Gatot Yulianto; Sugeng Hari Wisudo; Luluk Dwi Wulan Handayani; Irza Arnita nur; Hadi Supardi; Audra Ligafinza; Luisa Febrina Amalo; Marfian Dwidima Putra; Yusli wardiatno; Hefni Effendi (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Marine pollution can have a negative impact on aquaculture. For this reason, an appropriate and precise compensation calculation formula is needed. This study aims to formulate a formula for compensation calculating for aquaculture by reconstructing formula in PermenLH No. 7/2014. The reconstruction of formula was analyzed descriptively qualitatively with an expert judgement approach. The results showed that production data was a key factor in the reconstruction of compensation calculation formula. There are three reconstruction results formulas, namely compensation formula for aquaculture whose production data is available before and after pollution; compensation formula for aquaculture which only production data is available before pollution; and compensation formula for aquaculture which production data are not available